Downregulation of cGAS/STING expression in tumor cells by cancer-associated fibroblasts in colorectal cancer - Ryo Kanoda; Shotaro Nakajima; Hirokazu Okayama; Akinao Kaneta; Shun Chida; Takuro Matsumoto; Katsuharu Saito; Tomohiro Kikuchi; Yuya Maruyama; Hiroya Suzuki; Kosaku Mimura; Motonobu Saito; et al. (Scientific Reports)
Abstract The tumor cell-intrinsic cyclic GMP–AMP synthase (cGAS)–stimulator of interferon genes (STING) pathway is critical for activating anti-tumor immunity and enhancing immune checkpoint blockade therapy in colorectal cancer (CRC). Cancer-associated fibroblasts (CAFs), key components of the CRC tumor microenvironment, negatively regulate the anti-tumor immune response. However, their impact on tumor cell-intrinsic cGAS–STING expression remains unclear. In the present study, we investigated whether CAFs can downregulate cGAS–STING expression in CRC. We found that cGAS–STING expression in tumor cells inversely correlated with stromal expression of versican (VCAN), an immunosuppressive CAF marker, in CRC tissues. Co-culture experiments using primary human CAFs derived from CRC tissues revealed that CAFs downregulated cGAS and/or STING expression in CRC cell lines (WiDr, LoVo, HCT116). Furthermore, CAFs expressing VCAN and fibronectin 1 appeared to mediate this suppression. These findings suggest that immunosuppressive CAFs contribute to the downregulation of tumor cell-intrinsic cGAS–STING expression in CRC. Therefore, targeting CAFs to restore cGAS–STING expression may represent a promising strategy to enhance the efficacy of CRC treatment.